Examining the role of hybrid products in a consumer animosity setting - Kea, Garick; Phau, Ian (School of Marketing, Curtin Business School, 2008)
This paper aims to examine the effects of animosity on consumers? willingness to buy hybrid products (i.e. products that involve affiliations of two or more countries - such as branded in Japan but made in China). By examining the Chinese consumers? animosity towards the Japanese, the study?s findings revealed a high level of animosity present that resulted in the Chinese consumers? unwillingness to buy Japanese products. More importantly, results showed that the Chinese consumers are not any more receptive to hybrid products as such domestic affiliations have not diluted the animosity.